Introduction: The Rise of Fintech - Andrew F. Tuch (Washington University Journal of Law & Policy, 2020)
The use of technology has long accompanied the provision of financial products and services. In the late 1950s, financial institutions turned to information technology to help settle and record transactions, a burden that had grown with the surging volume of securities trades. These changes have only accelerated in recent years. Technology giants—the likes of Amazon, Apple, Facebook, and Google—are entering financial services, beginning to offer credit cards and currencies as they attempt to push more fully into retail banking. This volume of the Washington University Journal of Law and Policy examines fintech, focusing on the regulatory and other challenges it poses. The symposium benefits from contributions by prominent scholars of financial and securities regulation. These contributions examine the structure of firms and markets, considering fintech activities occurring within existing firms and regulatory perimeters and activities that spill over the boundaries we currently take for granted.
Keywords: fintech; financial; financial services; financial technology; finance; finance law; law; technology law; securities regulation; sec reg